Imatinib-loaded gold nanoparticles inhibit proliferation of fibroblasts and macrophages from systemic sclerosis patients and ameliorate experimental bleomycin-induced lung fibrosis - Codullo, Veronica; Cova, Emanuela; Pandolfi, Laura; Breda, Silvia; Morosini, Monica; Frangipane, Vanessa; Malatesta, Manuela; Calderan, Laura; Cagnone, Maddalena; Pacini, Chiara; Cavagna, Lorenzo; Recalde, Helios; et al. (Journal of Controlled Release, 2019)
Interstitial lung involvement in Systemic Sclerosis (SSc-ILD) is a complication with high morbidity and mortality. Specifically, engineered gold nanoparticles (GNPs) are proposed as targeted delivery system increasing efficacy of drugs with antifibrotic effect, such as tyrosine kinases. We aimed to test in vitro and in vivo the activity of targeted Imatinib (Im)-loaded GNP on SSc-ILD patients derived cells and in experimental model of lung fibrosis. GNPs functionalized with anti-CD44 and loaded with Im (GNP-HCIm) were synthesized. Lung fibroblasts (LFs) and alveolar macrophages from bronchoalveolar lavage fluids of SSc-ILD patients were cultured in presence of nanoparticles. GNP-HCIm significantly inhibited proliferation and viability inducing apoptosis of LFs and effectively reduced IL-8 release, viability and M2 polarization in alveolar macrophages. Anti-fibrotic effect of tracheal instilled GNP-HCIm was evaluated on bleomycin lung fibrosis mouse model comparing effect with common route of Im administration. GNP-HCIm were able to reduce significantly lung fibrotic changes and collagen deposition. Finally, electron microscopy revealed the presence of GNPs inside alveolar macrophages. These data support the use of GNPs locally administered in the development of new therapeutic approaches to SSc-ILD.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Gold nanoparticles; Imatinib; Inhalatory delivery; Interstitial lung fibrosis; Systemic sclerosis